Beautiful Melodies Telling Me Terrible Things: The Future of Race and Genetics for Scholars and Policy-Makers. Issue 1 (September 2015) - Hughey, Matthew W.; Byrd, W. Carson
To conclude this volume, we first engage in a brief history of scientific racism and the extent to which it resonates with the public. We then attempt to explain why American society and culture continue to fall prey to the seduction of biological determinism and racial essentialism: (1) the DNA mystique, (2) scientific revolutions and paradigm shifts, (3) the ethno-politics of genetics, (4) dismissals of social science as "soft, " (5) the defense of biology against reactionary dismissals, and (6) the aura of "objectivity" surrounding genetics. Last, we point to a way forward that may help scholars and the public avoid a return to old and debunked theories: (1) engagement with interdisciplinary fields and science and technology studies, (2) involvement of knowledgeable scholars and policy experts in government and higher education, (3) revision of the current additive funding model used by federal agencies, and (4) evolution in the training of future and current scholars and policy-makers toward mitigating inequality.